KAJIAN NUMERIK PENGARUH PENAMBAHAN ENERGY SAVING DEVICE JENIS WAKE EQUALIZING DUCT PADA KINERJA PROPELLER - Muhamad Andika Prasetyo; Burniadi Moballa; Daisy Dwijati Kumala Ratna (Politeknik Perkapalan Negeri Surabaya, 2023)
In recent years, research in the marine field has focused on reducing exhaustemissions by increasing fuel efficiency and carbon dioxide emissions. Reducing carbonemissions in the industry can be achieved by using energy-saving devices that also functionto reduce fuel consumption. This device also serves to reduce frictional resistance at theship’s aft so that energy losing impact to fuel consumption can be prevented. Based on thiscondition, this study uses an wake equalizing duct type with symmetrical and asymmetricalNACA variations. The CFD (Computational Fluid Dynamics) method is used to analyze thecoefficient of thrust and coefficient of torque. The duct is added to increase the value of bothcoefficients. The analysis without NACA variations results thrust coefficient value of 0.1442and torque coefficient value of 0.01539. The NACA 0015 variation produces thrustcoefficient value of 0.215747279, torque coefficient value of 0.020711813 and its efficiencyincreases 10%. NACA 4412 variation produces thrust coefficient value of 0.208392027,torque coefficient value of 0.020178827 and its efficiency (?o) increases by 11%. Theconclusion is additional wake equalizing duct is able to align the flow at the ship’s aft so thatit can minimize the occured turbulent current.